Air Pollution XX 2012
DOI: 10.2495/air120311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outdoor and indoor dust deposition as environmental pollution in Erbil province

Abstract: Since particulates are a sort of air pollution and seriously impact on environmental conditions, a considerable amount of programs to assess and control air pollution are regarded, since there are only a few studies on dust deposition in Iraq and since there have been drought conditions in last few years. In the Iraqi Kurdistan region, an experiment on dust accumulation as indoor and outdoor air pollution was undertaken in Erbil City and surrounding areas from November 2008 to April, 2009. The amount of deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The amount of dry deposition which occurred in the process of transportation and dust and sand storm and the distribution of elemental dust were not very different with previously collected data in Kurdistan Region (Aziz and Dabagh, 2012). Lai et al (2007) showed that the abundance of Pb, Cd and Fe in the atmosphere might occur as the result of vehicle exhaust emissions, industrial discharge, oil lubricants, and automobile parts along with the corrosion of building materials.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The amount of dry deposition which occurred in the process of transportation and dust and sand storm and the distribution of elemental dust were not very different with previously collected data in Kurdistan Region (Aziz and Dabagh, 2012). Lai et al (2007) showed that the abundance of Pb, Cd and Fe in the atmosphere might occur as the result of vehicle exhaust emissions, industrial discharge, oil lubricants, and automobile parts along with the corrosion of building materials.…”
Section: Discussionmentioning
confidence: 65%
“…Considerable amount of techniques and programs to mitigate and assess air pollution are regarded, there have been few studies on dust fall and their health and environmental consequences as Iraq have been facing a drought condition in the last decade. A study by (Aziz and Dabagh, 2012) in Erbil on evaluation of outdoor and indoor dust deposition found that decomposed dust were not more than limited values or levels of most of other countries. Natural and anthropogenic air pollutants can be transported in the atmosphere from original places for long distances (Varga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%